High flux thin film nanocomposite membrane incorporated with functionalized TiO2@reduced graphene oxide nanohybrids for organic solvent nanofiltration. (31st August 2019) - Abadikhah, Hamidreza; Kalali, Ehsan Naderi; Behzadi, Shabnam; Khan, Sayed Ali; Xu, Xin; Shabestari, Marjan E.; Agathopoulos, Simeon
Graphical abstract: Highlights: TiO2 @rGO nanohybrid was synthesized by a rapid microwave-assisted method. Amino functionalized TiO2 @rGO was successfully incorporated in TFN membrane. Solvent channelization and super hydrophilicity of TiO2 @rGO have improved nanofiltration performance. Antifouling properties were improved with TiO2 @rGO incorporation. Abstract: In this paper, graphene oxide based nanohybrids decorated with TiO2 nanoparticles (TiO2 @rGO) were synthesized and incorporated into the thin film nanocomposite (TFN) membrane for efficient organic solvent nanofiltration (OSN) with antifouling properties. In order to improve the compatibility of TiO2 @rGO in the polyamide active layer, the nanohybrids were amino-functionalized before their incorporation in the interfacial polymerization process. TiO2 @rGO incorporated TFN membranes showed intense permeability increment and antifouling characteristics in comparison with the controlled composite membrane and graphene oxide (GO) incorporated TFN membrane. The GO nanosheets structure favors solvent channeling and TiO2 provides super hydrophilic characteristics, both resulted in a super permeable-hydrophilic OSN membrane with high structural stability and premium antifouling properties.